MEMAHAMI PERKEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM - Agus Riswandi; Tika Yudiah Ningsih (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2023)
The curriculum is a learning framework developed by the Ministry of Education and Culture of the Republic of Indonesia as a guide for teachers in designing learning at the primary and secondary education levels. The main aim of the curriculum is to develop skills and knowledge that meet the needs of society and work life. Included in the PAI curriculum, the curriculum alone has gone through many developments from time to time. Curriculum development is caused by several foundations and aspects. The curriculum is built based on a competency approach that emphasizes developing students' abilities in solving problems, solutions, analyzing, thinking critically, communicating, and working together. The PAI curriculum also emphasizes integrated and contextual learning, where learning materials are related to religious life in everyday life and social reality, so that students can develop a deeper understanding of the relationship between knowledge and religious life.